Effect of Dimethyl Sulfoxide Primer Application Before a Two-Step Etch-and-Rinse Adhesive on the Microtensile Bond Strength and Nanoleakage - Ismail, Omar Abdelaziz; Hassanein, Olfat Elsayed; Hafez, Randa; Mamdouh, Mai (Wolters Kluwer, 2025)
Aims: This study investigates the impact of low concentrations of dimethyl sulfoxide (DMSO) on the stability of the dentinal hybrid layer formed using a two-step etch-and-rinse adhesive. Materials and Methods: Midcoronal dentine surfaces of 21 extracted molars were etched and randomly recruited into the study groups. This experimental study involved extracting wisdom teeth, preserving them at 4°C in 0.9% sodium chloride with 0.02% sodium azide, sectioning and polishing them, and randomly assigning them to three groups (n = 7/group) for DMSO pretreatment (1% DMSO/water [H 2 O], 10% DMSO/H 2 O, or no treatment/controls) in preparation for microtensile bond strength assessment and the sectioned beams (0.9 mm 2) where all were subjected to tension until fracture after storage for 24 h after soaking into artificial saliva for 12 months. In addition, nanoleakage assessment was conducted using scanning electron microscopy. The findings were computed statistically using analysis of variance and Tukey's tests (α=0.05). Results: The results revealed that immediate bond strength had no significant difference between the three groups (P > 0.05). After aging, the control group showed diminished bond strengths less than that of intervention for 1 and 10% DMSO solutions (P < 0.05). Regarding nanoleakage, the aged control group showed the highest level of silver infiltration along the hybrid layer. Approximately, 10% of treatment with DMSO in the aged group showed significantly less nanoleakage compared with using a concentration of 1%. Conclusions: This study concludes that dentinal pretreatment using DMSO minimizes hybrid layer degradation and improves bond strength in adhesive restorations. It was also inferred that higher concentrations of DMSO may provide a better seal at the tooth-restoration interface within limits.